Dissemination and implementation of evidence-based programs for people with chronic disease: the impact of the COVID-19 pandemic - Coyle, Peter; Tripken, Jennifer; Perera, Subashan; Juarez, Gardenia A.; Spencer-Brown, Lesha; Cameron, Kathleen; Brach, Jennifer S. (Frontiers in Public Health, 2024)
Background Using the RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) framework, we describe the implementation of evidence-based chronic disease self-management education (CDSME) programs by the Administration for Community Living CDSME Grantees during 2016–2022 and we also explore the impact of the COVID-19 pandemic on implementation. Methods Grantees collected data before and after the implementation of the CDSME programs and contributed to the national data repository. Data components included workshop information, participant information, and organizational data. Results The cohort consisted of 175,973 individuals who participated in 34 CDSME programs across 45 states. Participants had a mean ± SD age of 66.1 ± 14.8 years, were primarily female (65.9%) and had a mean ± SD of 2.6 ± 2.3 chronic conditions. Compared to the pre-COVID-19 strata, those who participated during COVID-19 were on average 1.5 years younger and had slightly less comorbidities. For individuals who had pre and post program self-reported health, 65.3% stayed the same, 24.4% improved, and 10.3% worsened (p < 0.001) after participating in CDSME programs. Conclusion CDSME offers a variety of programs across a broad geographic area to a diverse set of older adults in the US, underscoring the expansive reach of this public health initiative. COVID-19 appears to have shifted participant reach toward a slightly younger and healthier population. Finally, these programs appear to be effective in improving participants’ self-rated health. However, these results should be interpreted with caution, given limitations due to missing data and the observational nature of this study design.